The Effect Of Profit Sharing Rate, Financing To Deposit Ratio (FDR), And Inflation Rate On The Number Of Mudharabah Deposits In Islamic Commercial Banks (Bus) - Nikmaturrohmah, Nikmaturrohmah; Priyojadmiko, Eko (Jurnal Riset Bisnis dan Manajemen Tirtayasa, 2023)
This study aims to determine the effect of Profit Sharing Rates, Financing to Deposit Ratio (FDR), and Inflation Rates on Total Mudharabah Deposits at Islamic Commercial Banks (BUS) for the 2017-2022 period. Using quantitative research methods with research locations at Islamic Commercial Banks. Sampling using purposive sampling with a total of 60 samples. The data analysis technique used is multiple linear regression analysis with hypothesis testing by means of the t test (partial) and the F test (simultaneous). Tests in this study used SPSS 26. The results showed that the Profit Sharing Rate had a positive and significant effect on Total Mudharabah Deposits with a tcount of 3.338 > ttable value of 1.673, FDR had a negative and significant effect on Total Mudharabah Deposits with tcount -2.527 > ttable value of 1.673, and the inflation rate has no significant effect on total mudharabah deposits with a tcount of 1.528 <1.673. Simultaneously, the Profit Sharing Rate, FDR, and the Inflation Rate affect the Total Mudharabah Deposits with Fcount 219.241 > Ftable 2.77. Then, based on the Adjusted R Square result of 0.769, it shows that the ability of the independent variable to explain the dependent variable is 76.9%, the remaining 23.1% is explained by other variables not included in this study.